2021
DOI: 10.1039/d1nj00397f
|View full text |Cite
|
Sign up to set email alerts
|

Rare proximity enforced copper hydrogen interactions in copper(i)-chalcogenones

Abstract: The copper(I) chalcogenones with a rare Cu····H—C(sp3) hydrogen bonding interactions have been reported. The copper(I) bis(benzimidazole-2-chalcogenone) complexes [Cu(L1)4]+BF4- (1) and [Cu(L2)4]+BF4- (2) (L1 = bis(1-isopropyl-benzimidazole-2-selone)-3-ethyl; L2 = bis(1-isopropyl-benzimidazole-2-thione)-3-ethyl) have been...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…The 1‐isopropyl imidazole, 2‐bromopyridine, triphenylphosphine and solvents were purchased from commercial sources. 3‐isopropyl‐1‐(pyridin‐2‐yl)‐imidazolium bromide was synthesized as described in the literature [32] . L was synthesized under an inert gas atmosphere using standard Schlenk line techniques, while 1 – 6 were synthesized under ambient conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The 1‐isopropyl imidazole, 2‐bromopyridine, triphenylphosphine and solvents were purchased from commercial sources. 3‐isopropyl‐1‐(pyridin‐2‐yl)‐imidazolium bromide was synthesized as described in the literature [32] . L was synthesized under an inert gas atmosphere using standard Schlenk line techniques, while 1 – 6 were synthesized under ambient conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the presence of selenium in the ligand core provides additional stability to the catalyst in an oxidative environment due to the weak selenium–oxygen bond, 36–40 and consequently, selenocysteine has been utilized in the [NiFe]-hydrogenase enzyme. 12 [NiFeSe] hydrogenase enzymes exhibit HER activity 40 times greater than the parent [NiFe] hydrogenase enzyme (Chart 1).…”
Section: Introductionmentioning
confidence: 99%
“…25,28,[30][31][32] In this context, the elements of the 4 th period, especially selenium, can be useful for electrocatalytic activity as these elements provide the architecture of soft donor ligands, which stabilize the low-valent oxidation states of 3d-metal ions. [33][34][35] Furthermore, the presence of selenium in the ligand core provides additional stability to the catalyst in an oxidative environment due to the weak selenium-oxygen bond, [36][37][38][39][40] and consequently, selenocysteine has been utilized in the [NiFe]hydrogenase enzyme. 12 [NiFeSe] hydrogenase enzymes exhibit HER activity 40 times greater than the parent [NiFe] hydrogenase enzyme (Chart 1).…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Several research groups have reported the synthesis of monodentate, and multidentate hybrid telluroether ligands and studied their coordination behaviour with various transition metal ions such as; Ru, Rh, Ni, Pd, Pt, Cu and Ag. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] However, the isolation of bimetallic complexes has not been explored well despite their interesting structural properties and scope of the study of the metal•••metal interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The polytelluroethers have been relatively less studied as compared with their polythioether and polyselenoether analogues because of their poor stability and easy decomposition at room temperature in the oxygen environment due to weak C−Te bond and low oxidation potential of tellurium [3,4] . Several research groups have reported the synthesis of monodentate, and multidentate hybrid telluroether ligands and studied their coordination behaviour with various transition metal ions such as; Ru, Rh, Ni, Pd, Pt, Cu and Ag [5–22] . However, the isolation of bimetallic complexes has not been explored well despite their interesting structural properties and scope of the study of the metal⋅⋅⋅metal interactions.…”
Section: Introductionmentioning
confidence: 99%